2012
DOI: 10.1073/pnas.1213438109
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of human Cdc20 supports multisite degron recognition by APC/C

Abstract: The anaphase-promoting complex/cyclosome (APC/C) promotes anaphase onset and mitotic exit through ubiquitinating securin and cyclin B1. The mitotic APC/C activator, the cell division cycle 20 (Cdc20) protein, directly interacts with APC/C degrons––the destruction (D) and KEN boxes. APC/C Cdc20 is the target of the spindle checkpoint. Checkpoint inhibition of APC/C Cdc20 requires the binding of a BubR1 KEN box to Cdc20. How APC/C recognizes substrates is not under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
97
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 40 publications
3
97
0
1
Order By: Relevance
“…Protein Expression and Purification-The full-length Cdc20, Cdc20 WD40 (residues 161-477), and Mad2 L13A proteins were purified as previously described (16,32). The coding regions of various fragments of the human BubR1 middle region (BubR1M) were cloned into the pGEX-6p vector (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Protein Expression and Purification-The full-length Cdc20, Cdc20 WD40 (residues 161-477), and Mad2 L13A proteins were purified as previously described (16,32). The coding regions of various fragments of the human BubR1 middle region (BubR1M) were cloned into the pGEX-6p vector (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…Structural studies of Cdc20 and Cdh1 have revealed similar APC/C degron-binding surfaces in these activators (15)(16)(17). They each contain a single, highly conserved KEN box-binding site on the top face of the ␤ propeller formed by their WD40 domain and a D box-binding site at the side of the ␤ propeller (Fig.…”
Section: Human Bubr1mmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein p31 binds to Mad2 and removes it from the MCC leading to sub stoichiometric levels of Mad2 in the MCC 21 . An N-terminal KEN box motif in BubR1 is critical for stable binding to Cdc20 and binds to conserved residues on the top side of the WD40 domain 17,19,[22][23][24][25] . BubR1 in vertebrates also contains an internal Cdc20 binding domain (referred to here as IC20BD) that binds the Cdc20 WD40 domain in a Mad2-independent manner 6,26,27 .…”
mentioning
confidence: 99%